2010
DOI: 10.1021/jp103716r
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Interactions of Ru Dye with Iodide Ions and Nitrogen-Containing Heterocycles in Dye-Sensitized Solar Cells

Abstract: Iodide ions and nitrogen-containing heterocycles, including 4-t-butylpyridine, are fundamental in the electrolyte solution of dye-sensitized solar cells as a redox and a promotive additive, respectively. Although discrete interaction of iodide ions and of heterocycles with the sensitizing dye is known, their simultaneous interaction with the dye and its effect on dye-sensitized solar cell performance is still an open question. In this paper, we have studied simultaneous interactions of iodide ions and N-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…They also proposed that by using bipyridyl anchoring groups having both pyridine groups bind to TiO 2 anode so that the dye molecule stands perpendicular to the TiO 2 surface, opening the binding sites for reacting with the iodide ions. These studies, however, did not clearly show what the regeneration sites of the oxidized dye were in general, or how to enhance the interaction of the iodide ion with the regeneration sites in particular.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…They also proposed that by using bipyridyl anchoring groups having both pyridine groups bind to TiO 2 anode so that the dye molecule stands perpendicular to the TiO 2 surface, opening the binding sites for reacting with the iodide ions. These studies, however, did not clearly show what the regeneration sites of the oxidized dye were in general, or how to enhance the interaction of the iodide ion with the regeneration sites in particular.…”
Section: Introductionmentioning
confidence: 88%
“…(7)), which is probably the minor dye regeneration step. However, even though have been many experimental 9,[11][12][13][14]19,20 and theoretical 8,17,[21][22][23][24][25][26][27][28][29][30][31] studies focusing on the dye regeneration process, detailed structures of the involved intermediates and the regeneration sites of the dye cation have not been fully understood. Consequently, strategies for increasing the dye regeneration rate by molecular structure design to improve the photovoltaic performance of the dye molecules are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These phenomena suppress electron transfer from the conduction band of TiO 2 to I À 3 (Huang et al, 1997;Rijnberg et al, 1998;Hara et al, 2004;Shi et al, 2005), and increase the V oc . Kusama et al (2010) suggested that TBP can directly bind to the carboxyl groups in Ru dye via two hydrogen bonds. If the carboxyl groups in Flemion similarly bind to TBP, many of the TBP molecules would be trapped within the Flemion matrix, thereby lowering the concentration of adsorbed TBP at the TiO 2 surface and reducing the V oc relative to non-Flemion-based electrolytes.…”
Section: Photovoltaic Performance Of the Dsscsmentioning
confidence: 99%